A Rare Presentation of Rapunzel Syndrome without Intestinal Obstruction with Review of Literature - Garg, Neha; Verma, Surender; Garg, Pradeep; Mehta, Anil; Pal, Vijay; Agarwal, Shivika (Indian Journal of Case Reports, 2020)
Trichobezoar with Rapunzel syndrome is an uncommon diagnosis. Its clinical presentation without intestinal obstruction is rare. It is predominantly found in mentally retarded or emotionally disturbed youngsters. They typically cause abdominal pain and vomiting but can also present as asymptomatic abdominal mass progressing to obstruction and perforation; however, our case of trichobezoar presented with early satiety and loss of weight. The diagnosis was confirmed on computed tomography scan. The trichobezoar was removed by the anterior gastrotomy under general anesthesia. The post-operative period was uneventful. We recommend conventional laparotomy and anterior gastrotomy for large size trichobezoars extending to the duodenum and jejunum as the treatment of choice. Psychiatric consultation is recommended to prevent relapse.